Accounting in Theory Development: A Systematic Literature Review - Mery Rohaya Sihombing; Enggar Diah Puspa Arum (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to identify and explore the development of accounting theory during the period 2012–2022. Using a Systematic Literature Review (SLR) approach, this study analyzes the main trends, dominant theories, and the relevance of accounting theory to modern business practices and needs. Data were collected through Publish or Perish 8 (PoP 8) software with a literature restriction that included articles related to normative and positive accounting theory, published in reputable journals during the period. The results show that accounting theory continues to evolve from a pragmatic to a positive approach, with each phase making important contributions to enriching the discipline. Methodological analysis shows the dominance of qualitative approaches, while quantitative approaches continue to validate the relationships between variables. Furthermore, international contributions demonstrate the strong influence of globalization and technology, including artificial intelligence (AI), in driving the development of accounting theory and practice. This study concludes that accounting theory must continue to be refined to address local and global challenges. A combination of local and global approaches is needed to produce more relevant, inclusive, and sustainable theory.